1997
DOI: 10.1093/hmg/6.9.1605
|View full text |Cite
|
Sign up to set email alerts
|

Connexin26 mutations associated with the most common form of non- syndromic neurosensory autosomal recessive deafness (DFNB1) in Mediterraneans

Abstract: Non-syndromic neurosensory autosomal recessive deafness (NSRD) is the most common form of genetic hearing loss. Previous studies defined at least 15 human NSRD loci. Recently we demonstrated that DFNB1, located on the long arm of chromosome 13, accounts for approximately 80% of cases in the Mediterranean area. Further analysis with additional markers now identifies several recombinants which narrow the candidate region to approximately 5 cM, encompassed by markers D13S141 and D13S232 and including several ESTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
411
5
23

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 584 publications
(448 citation statements)
references
References 19 publications
9
411
5
23
Order By: Relevance
“…Approximately 12% of these individuals were identified as having mutations in the GJB2 gene responsible for the hearing loss. This frequency is lower than previously reported frequencies, suggesting a unique population, small numbers, or that the frequency in newborn samples may be lower because the study included milder cases [Denoyelle et al, 1997;Zelante et al, 1997]. The discrepancy in frequency of GJB2 mutations in these studies underscores the need for further study and proper classification of cases.…”
Section: Introductioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Approximately 12% of these individuals were identified as having mutations in the GJB2 gene responsible for the hearing loss. This frequency is lower than previously reported frequencies, suggesting a unique population, small numbers, or that the frequency in newborn samples may be lower because the study included milder cases [Denoyelle et al, 1997;Zelante et al, 1997]. The discrepancy in frequency of GJB2 mutations in these studies underscores the need for further study and proper classification of cases.…”
Section: Introductioncontrasting
confidence: 63%
“…To date, 79 loci for nonsyndromic hearing loss have been identified: 40 autosomal dominant, 34 autosomal recessive, and 5 X-linked [Hereditary Hearing Loss Homepage, 2003]. Multiple studies have shown that mutations in the single GJB2 gene may account for up to 50% of nonsyndromic sensorineural autosomal recessive hearing loss or 20% of all childhood hearing loss [Denoyelle et al, 1997;Zelante et al, 1997;Cohn et al, 1999;Green et al, 2002]. The GJB2 gene encodes the connexin 26 protein, which is involved in gap junction formation allowing cell-to-cell diffusion and the transfer of ions between neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an extremely heterogeneous disorder in which at least 30 reported loci [Van Camp et al, 1997;Zbar et al, 1998;Keats and Berlin, 1999] and mutations in one gene (GJB2) have been shown to be major cause of ARNSD in many different populations [Maw et al, 1995;Gasparini et al, 1997;Kelsell et al, 1997;Park et al, 2000;Morell et al, 1998;Zelante et al, 1997]. We have studied the mutation load of GJB2 in the Iranian population and have found the prevalence to be much lower than in other studied populations (Najmabadi et al, 2001; submitted manuscript).…”
Section: New Mutations; Rare and New Genesmentioning
confidence: 99%
“…This nucleotide deletion can occur at position 35 (35delG) or at position 30 (30delG) of the gene, but the deletion at position 35 (35delG), genetically related to chromosome 13, is the more frequent one, varying between approximately 50% to 85% of the non-syndromic deafness cases in patients from Italy, Spain, and Israel 7,[11][12][13] . In a study with Brazilian patients14, mutations in gene GJB2 were found in 22% of families tested with at least one patient with hearing loss, and in 11.5% of cases in which an environmental etiology was not completely ruled out.…”
Section: Introductionmentioning
confidence: 99%